Impact of the new scoring system on expert table tennis players` activity - Seve, C. (Journal of Sports Sciences, 2006)
The activity of expert table tennis players during matches under the old scoring system has been studied within the French Table Tennis Federation. The results showed that the players` actions were organized to form sequences dividing each match into phases of exploration and execution (Sève, 2002, Table Tennis Sciences, 4 & 5, 167-176; Sève, Saury, Theureau & Durand, 2002, Cognitive System Research, 3, 501-522). Matches began with an inquiry period during which the players looked for strokes that impinged upon the opponent's play. Regardless of the outcome of the inquiry phase, however, it had to come to an end when the players felt they could no longer afford to sacrifice points for fear of losing the match. On September 1, 2001, the scoring system changed, and the goal of the present study was to evaluate the impact of this new system on elite table tennis players` activity during matches.